Enhancing English Proficiency and Digital Literacy through Digital Storytelling in Vocational Health Students - Istanto, Wisnu; Amelia, Noer; Edi-Krause, Sulistyaning; Suemith, Merlissa (Universitas Hamzanwadi, 2024)
Teaching English to healthcare students presents multifaceted challenges, particularly for non-native speakers who must concurrently navigate the complexities of medical concepts and the acquisition of language proficiency. Addressing these dual demands necessitates pedagogical innovations that integrate linguistic development with digital literacy to meet the dynamic requirements of contemporary healthcare. This quasi-experimental study explored the efficacy of digital storytelling as a transformative educational tool for enhancing English fluency and multimedia communication skills among vocational health students. Seventy-eight participants were allocated into an experimental group, which engaged in structured weekly digital storytelling activities, and a control group, which adhered to traditional grammar-based instruction. Over a 16-week intervention, data collected via the Test of English Proficiency Speaking and the Multimedia Communication Comfort Scale revealed significant outcomes, with the experimental group exhibiting substantial improvements (T-value = -23.91, p < 0.001) compared to the negligible gains of the control group (T-value = -11.12, p > 0.05). Furthermore, a robust positive correlation (r = 0.60) between initial lower proficiency and more significant improvement underscores the inclusivity and adaptability of digital storytelling for diverse learner profiles. By merging authentic language use with practical engagement in digital tools, digital storytelling equips vocational health students with critical competencies essential for effective communication in increasingly digitalized healthcare environments, demonstrating its potential as a cornerstone of 21st-century vocational education.